Skip to content

Instantly share code, notes, and snippets.

@tensorpudding
Created September 15, 2009 13:56
Show Gist options
  • Save tensorpudding/187306 to your computer and use it in GitHub Desktop.
Save tensorpudding/187306 to your computer and use it in GitHub Desktop.
Suppose that:
f(n)*f(n-2) - f(n-1)^2 = (-1)^(n-1) (1)
This is the same as the assumption, but for n-1. The inductive step requires us to show that it is true for n:
f(n+1)*f(n-1) - f(n)^2 = (-1)^n (2)
We notice that:
(-1)^n = -1*(-1)^(n-1) (3)
so we replace (-1)^(n-1) by the LHS of (1) and we get:
f(n+1)*f(n-1) - f(n)^2 = (-1) * [ f(n) * f(n-2) - f(n-1)^2 ]
and we distribute and rearrange to match terms, to get:
f(n-1) * [ f(n+1) - f(n-1) ] = f(n) [ f(n) - f(n-2) ]
But we know that f(n+1) - f(n-1) = f(n), and f(n) - f(n-2) = f(n-1), so we have:
f(n-1)*f(n) = f(n) * f(n-1)
which is obviously true, and therefore we have demonstrated the inductive step.
Sign up for free to join this conversation on GitHub. Already have an account? Sign in to comment